Pengaruh Literasi Keuangan dan Pengalaman Investasi terhadap Pengambilan Keputusan Investasi Saham di Bursa Efek Indonesia - Pramanaswari, AA Sagung Istri (Universitas Katolik Widya Karya Malang, 2025)
This study looks at how far knowledge about money and experience with investments affect choices on stocks in the Indonesian capital market. 420 buyers filled out an online form that was used with a causal associative quantitative method to gather data. The study's results show that both knowledge about money and experience with investments have a good and significant effect on stock investment choices, sometimes at the same time. The coefficient of determination (R²) of 47.6% shows that the two factors can explain almost half of the differences in how buyers choose to spend their money. This study shows how important it is to learn more about money and make more investments in order to make smart investments in the capital market, because the market is always changing. This study also has real-world effects for investors, financial institutions, and officials who deal with ways to help Indonesian small investors do better.